2012
DOI: 10.1128/iai.00144-12
|View full text |Cite
|
Sign up to set email alerts
|

Members of the Francisella tularensis Phagosomal Transporter Subfamily of Major Facilitator Superfamily Transporters Are Critical for Pathogenesis

Abstract: ABSTRACTFrancisella tularensisis the causative agent of tularemia. Due to its aerosolizable nature and low infectious dose,F. tularensisis classified as a category A select agent and, therefore, is a priority for vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 43 publications
2
31
0
Order By: Relevance
“…For example, deletion of phtA in Legionella pneumophila (32) and three phtA orthologues in Francisella tularensis resulted in reduced intracellular growth and attenuation (33). However, while deletion of icgA did not affect growth in broth, it significantly enhanced intracellular growth compared to that of the wild-type strain.…”
Section: Figmentioning
confidence: 97%
“…For example, deletion of phtA in Legionella pneumophila (32) and three phtA orthologues in Francisella tularensis resulted in reduced intracellular growth and attenuation (33). However, while deletion of icgA did not affect growth in broth, it significantly enhanced intracellular growth compared to that of the wild-type strain.…”
Section: Figmentioning
confidence: 97%
“…One of the more recent reports demonstrated the attenuation of three LVS mutants of a family of genes predicted to encode transporter proteins of the MFS family [26]. LVSΔ fptB , LVSΔ fptE , and LVSΔ fptG were all found to display altered intracellular replication kinetics in either J774.1 cells and/or HepG2 cells.…”
Section: Summary Of Recent Live Attenuated Lvs Mutantsmentioning
confidence: 99%
“…F. tularensis is predicted to encode 31 MFS transporters. Characterization of a subset of MFS transporters revealed their role in pathogenesis and virulence of F. tularensis (Marohn et al, 2012). Bina et al (2008) identified and characterized AcrAB RND multidrug transporter.…”
Section: Introductionmentioning
confidence: 99%